DAMPAK PENGGUNAAN GADGET BERLEBIHAN TERHADAP PERILAKU DAN PRESTASI BELAJAR SISWA SD - Hanum Istiqomah Azhar Fadhila; Nadya Pramesti Akyela; Reza Nur Oktavia; Wildiana Rifqa Suriansyah; Ahmad Suriansyah; Wahdah Refia Refianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of digital technology has led to an increase in gadget use among elementary school students, which raises concerns regarding its impact on children’s behavior and academic achievement. Excessive gadget use, particularly for non-educational purposes, is suspected to negatively affect students’ concentration, social interaction, emotional stability, and learning outcomes. This study aims to comprehensively analyze the effects of excessive gadget use on the behavior and academic performance of elementary school students. The research employs a literature review method by examining various relevant scientific articles, books, and previous studies published in recent years. Data were analyzed using content analysis to identify patterns and findings related to gadget use intensity, behavioral changes, and learning achievement. The results indicate that excessive gadget use is closely associated with decreased learning concentration, reduced motivation, declining social interaction, emotional instability, and a tendency toward individualistic behavior. In addition, prolonged and uncontrolled gadget use contributes to sleep disturbances, which further impacts students’ readiness and academic performance at school. However, several studies show that the negative impacts may be mitigated through parental supervision, appropriate time management, and the use of gadgets for educational purposes. In conclusion, excessive gadget use has significant negative effects on both behavior and academic performance of elementary school students, highlighting the importance of collaborative efforts between parents, teachers, and schools to regulate and guide children’s gadget use more wisely.